Green City Concept (GCC) and it's submissive attachment among communities in Melaka / Zarina Mohd Zain, Thenmolli Vadeveloo and Suzei Mat Nurudin - Mohd Zain, Zarina; Vadeveloo, Thenmolli; Mat Nurudin, Suzei (2022)
With an increasing trend of urbanization, green city seeking for evolution from a traditional city paradigm to a sustainable city. Throughout the years there has been struggle in the development of the concept and programs of 'greening' however, such fast urban transformation has not been simple to manage. This paper aims to find out the level of understanding and awareness of communities on the Green City Concept. At the end, some discussion been made to compare the GCC in Melaka, Malaysia with Ho Chi Minh, and Hanoi in Vietnam. Total of 86 respondents reach during survey distributed among people who lived in Melaka. The findings show that, some programs and projects implemented by the government successfully supported the implementation of GCC however, to improve further, government can refer to the neighbour's state to fully develop the GCC Plan.